1994
DOI: 10.1099/00222615-41-3-191
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intestinal and extra-intestinal strains of enterotoxigenic Bacteroides fragilis by the HT-29 cytotoxicity assay

Abstract: Summary.Bacteroides fragilis strains with enterotoxic activity can be isolated from the faeces of newborn farm animals with diarrhoea and are called enterotoxigenic B. fragilis (ETBF). These strains can now be detected in an in-vitro cytotoxicity assay with HT-29 cells. In this study, 146 B. fragilis strains (95 faecal and 40 extra-intestinal isolates) and 64 Bacteroides isolates belonging to species other than B. fragilis were tested for their ability to produce enterotoxin. Sixteen strains of ETBF were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 7 publications
1
34
0
1
Order By: Relevance
“…Additional studies with infant and 2-weekold rabbits as well as adult rabbits with ligated ceca confirmed the enteropathogenicity of ETBF, but in these disease models bloody diarrhea and mortality were frequently observed (17,(65)(66)(67)(68). However, ETBF virulence was variable in rabbit models (66,67), consistent with subsequent observations that sterile culture supernatants of ETBF exhibited variable biologic activity on HT29/C1 cells (a human colonic epithelial tumor cell line) (13,30,82,116,119). Histopathologic abnormalities in these non-gnotobiotic animal models also occurred only in the distal ileum and colon, with disruption of the epithelial integrity and predominant neutrophilic or mixed neutrophilic and mononuclear cellular infiltrates in the lamina propria; animals colonized with NTBF strains exhibited normal colonic histopathology without inflammation by light microscopy.…”
Section: Experimental Etbf Infectionssupporting
confidence: 69%
See 1 more Smart Citation
“…Additional studies with infant and 2-weekold rabbits as well as adult rabbits with ligated ceca confirmed the enteropathogenicity of ETBF, but in these disease models bloody diarrhea and mortality were frequently observed (17,(65)(66)(67)(68). However, ETBF virulence was variable in rabbit models (66,67), consistent with subsequent observations that sterile culture supernatants of ETBF exhibited variable biologic activity on HT29/C1 cells (a human colonic epithelial tumor cell line) (13,30,82,116,119). Histopathologic abnormalities in these non-gnotobiotic animal models also occurred only in the distal ileum and colon, with disruption of the epithelial integrity and predominant neutrophilic or mixed neutrophilic and mononuclear cellular infiltrates in the lamina propria; animals colonized with NTBF strains exhibited normal colonic histopathology without inflammation by light microscopy.…”
Section: Experimental Etbf Infectionssupporting
confidence: 69%
“…In vivo expression of mpII or the role of MPII in ETBF disease pathogenesis has not yet been addressed. The culture supernatants of ETBF strains grown in vitro vary significantly in HT29/C1 cell biologic activity (13,30,82,116,119). Although the mechanism(s) accounting for this variation is incompletely understood, at least two mechanisms likely contribute to the variable biologic activity, including bft copy number (21) and transcriptional regulation of bft yielding different amounts of BFT secreted by ETBF strains (30).…”
Section: Genetics Of Etbfmentioning
confidence: 99%
“…Moreover, studies in vivo have showed that ETBF produce an accumulation of sodium, chloride, albumen, and protein. Despite of this fact, ETBF strains have been considered as enteropathogens to children and adults in several countries (Pantosti et al 1994(Pantosti et al , 1997. However, it seems to be too early to suggest that this protease is a determinant factor of the B. fragilis invasiveness, and more studies are needed, according to Ferreira et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Before the assay, the medium was removed and 180 µl of fresh medium without serum were added to each well, and then 20 µl of supernatant were added in each well, in duplicate. The plate was incubated at 37°C, in air plus 5% CO 2 and then examined after 3-4 h, period in which the typical toxin-induced cytotoxic changes occur (Pantosti et al 1994).…”
Section: Methodsmentioning
confidence: 99%
“…To test the biological activity of the precursor, a cytotoxicity assay for HT-29 cells was performed as described previously (6). The ability of the mouse antiserum to neutralize the enterotoxin was tested by the same assay (6).…”
mentioning
confidence: 99%